Implementing Public Policy - Michael Hill, Peter Hupe (Sage, 2007)
Building on the success of the previous two editions, this book provides students with an exemplary overview of the theory and practice of public policy implementation and how it relates to contemporary public management. In doing so, this new edition makes use of more illustrative examples, delves further into researching implementation and explores issues about the relationship between policy formulation and implementation in greater depth.